“The In-between Crowd”: Contrasting Representations of Minority Language Students - Lynne Wiltse (Language and Literacy: A Canadian Educational e-journal, 2011)
This paper examines contrasting representations of minority language students in a linguistically diverse junior high classroom in an urban area of Western Canada. The majority of the research participants was of Asian heritage, and spoke English as a second language. Drawing on the construct of learner identity, I explore how these minority language learners’ identities affected their experience in school. The study points to hybrid language practices, with particular attention to academic discourse, as a solution to developing English literacy in schools with students from multilingual backgrounds.